Optimalisasi Ketersediaan Pakan dengan Inovasi Ensilase pada Produktivitas Ternak Ruminansia Berkelanjutan di Kelompok Tani Lestari II - Rahmawati, Resti Yuliana; Winurdana, Alfan Setya; Suprajang, Sandi Eka; Puspitorini, Palupi; Sunandes, Aris (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
This community service program aims to enhance sustainable livestock feed production capacity through the application of silage technology in the Lestari III Farmer Group, Tegalrejo Village, Selopuro District, Blitar Regency. The main problem faced by the partners is the fluctuating availability of forage, abundant during the rainy season but scarce in the dry season. The offered solutions include technology transfer of silage production using fermentation boosters, business management training, and the application of digital branding strategies for product marketing. The implementation methods consist of socialization, technical training, mentoring, and continuous evaluation. The production target is 3,000 kg of silage per month or 30,000 kg per year, with surplus production sold as economically valuable reserve feed. The program results indicate improved farmers’ knowledge and skills in feed preservation, business management, and digital-based marketing. The impacts include continuous feed supply throughout the year, increased livestock productivity, improved business efficiency, market expansion, and increased farmer income. This program contributes to achieving the SDGs, particularly in the areas of decent work and economic growth, as well as responsible consumption and production.